The Influence Of The Implementation Of The Know Your Employee (KYE) Method On Increasing Employee Loyalty At PT Bank KB Bukopin KCU Kupang - Reisanty M. Djami; Surya S. Tarigan; Yesika Y. Mudin (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to determine the influence of the implementation of the Know Your Employee (KYE) method on increasing employee loyalty at PT Bank KB Bukopin Main Branch Office (KCU) Kupang. The KYE method is a managerial approach that focuses on a deep understanding of employees’ characteristics, needs, and potential in order to create a harmonious and productive work environment. This research employs a quantitative method with a descriptive-verificative approach. Data were collected through questionnaires distributed to all 32 employees of PT Bank KB Bukopin KCU Kupang and analyzed using a simple linear regression technique. The results of the study show that the implementation of the KYE method has a positive and significant effect on employee loyalty. This means that the better the management applies the KYE method, the higher the level of employee loyalty to the company. These findings indicate that a personal approach to understanding employees can enhance emotional attachment, job satisfaction, and organizational commitment. The study recommends that management continue to optimize the implementation of the KYE method through open communication, transparent career development, and the strengthening of a culture of appreciation in the workplace.